Chitosan and its derivatives regulate lactic acid synthesis during milk fermentation - Kurchenko, Vladimir; Halavach, Tatsiana; Yantsevich, Alexey; Shramko, Mariya; Alieva, Lyudmila; Evdokimov, Ivan; Lodygin, Alexey; Tikhonov, Vladimir; Nagdalian, Andrey; Ali Zainy, Faten M.; AL-Farga, Ammar; ALFaris, Nora Abdullah; et al. (Frontiers in Nutrition, 2024)
Introduction The influence of chitosan's physicochemical characteristics on the functionality of lactic acid bacteria and the production of lactic acid remains very obscure and contradictory to date. While some studies have shown a stimulatory effect of oligochitosans on the growth of Lactobacillus spp, other studies declare a bactericidal effect of chitosan. The lack and contradiction of knowledge prompted us to study the effect of chitosan on the growth and productivity of L. bulgaricus in the presence of chitosan and its derivatives. Methods We used high molecular weight chitosan (350 kDa) and oligochitosans (25.4 and 45.3 kDa). The experiment was carried out with commercial strain of L. bulgaricus and the low fat skim cow milk powder reconstituted with sterile distilled water. After fermentation, dynamic viscosity, titratable acidity, pH, content of lactic acid, colony forming units, chitosan and oligochitosans radii were measured in the samples. Fermented dairy products were also examined using sodium dodecyl sulfate electrophoretic analysis, gas chromatography-mass spectrometry and light microscopy. Results and discussion The results of the study showed that when L. bulgaricus was cultured in the presence of 25.4 kDa oligochitosans at concentrations of 0.0025%, 0.005%, 0.0075% and 0.01%, the average rate of LA synthesis over 24 hours was 11.0 × 10−3 mol/L/h, 8.7 × 10−3 mol/L/h, 6.8 × 10−3 mol/L/h, 5.8 × 10−3 mol/L/h, respectively. The 45.3 kDa oligochitosans had a similar effect, while the average rate of lactic acid synthesis in the control sample was only 3.5 × 10−3 mol/L/h. Notably, 350 kDa chitosan did not affect the rate of lactic acid synthesis compared with the control sample. Interestingly, interaction of chitosan with L. bulgaricus led to a slowdown in the synthesis of propanol, an increase in the content of unsaturated and saturated fatty acids, and a change in the composition and content of other secondary metabolites. The quantity of L. bulgaricus in a sample with 0.01% chitosan exceeded their content in the control sample by more than 1,700 times. At the same chitosan concentration, the fermentation process was slowed down, increasing the shelf life of the fermented milk product from 5 to 17 days while maintaining a high content of L. bulgaricus (6.34 × 106 CFU/g).